2021
DOI: 10.1111/jace.17754
|View full text |Cite
|
Sign up to set email alerts
|

Tuning the mechanical toughness of the metal nanoparticle‐implanted glass: The effect of nanoparticle growth conditions

Abstract: Excellent homogeneity of glass gives rise to high optical transparency and uniform properties, which make oxide glass a unique material for a variety of applications. 1 Further, glass can be easily shaped, and hence, it is suitable for mass production in uniform conditions. However, such homogeneity of glass induces tensile stress concentration at around a crack tip once a microcrack appears at the glass surface or a bubble is generated inside the glass. 2 Hence, the generation of high

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…In this ideal situation, the low stiffness of the droplets tends to attract the crack toward the tough droplets, which simultaneously induces some plastic energy dissipation (due to the change in crack direction) and forces the crack to propagate through the most cohesive regions of the glass . These behaviors have recently been confirmed in refs and , wherein it was suggested that toughness can be enhanced upon implantation of soft metal nanoparticles.…”
Section: Mechanical Propertiesmentioning
confidence: 78%
“…In this ideal situation, the low stiffness of the droplets tends to attract the crack toward the tough droplets, which simultaneously induces some plastic energy dissipation (due to the change in crack direction) and forces the crack to propagate through the most cohesive regions of the glass . These behaviors have recently been confirmed in refs and , wherein it was suggested that toughness can be enhanced upon implantation of soft metal nanoparticles.…”
Section: Mechanical Propertiesmentioning
confidence: 78%